2019
DOI: 10.1038/s41598-019-53541-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate-induced changes in carbon flows across the plant-consumer interface in a small subarctic lake

Abstract: Reconstructions of past food web dynamics are necessary for better understanding long-term impacts of climate change on subarctic lakes. We studied elemental and stable isotopic composition of sedimentary organic matter, photosynthetic pigments and carbon stable isotopic composition of Daphnia (Cladocera; Crustacea) resting eggs (δ13CClado) in a sediment record from a small subarctic lake. We examined how regional climate and landscape changes over the last 5800 years affected the relative importance of alloch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Our model linking δ 13 C Clado to sediment composition and algal groups was highly significant, emphasing that zooplankton diet is affected by both climate-induced changes in algal biomass (δ 13 C OM as a proxy of proportion of algal biomass in sediments) and community composition (PC1 pig ). These results confirm previous findings that the zooplankton diet and basal resources are closely linked, and that climate change is responsible for those changes (Belle et al, 2019;Rantala et al, 2015). thic and pelagic consumers in the long term (Belle et al, 2017(Belle et al, , 2018(Belle et al, , 2020.…”
Section: Trends and Fluctuations In Climate Algal Community And Carbon Resources For Zooplanktonsupporting
confidence: 91%
See 1 more Smart Citation
“…Our model linking δ 13 C Clado to sediment composition and algal groups was highly significant, emphasing that zooplankton diet is affected by both climate-induced changes in algal biomass (δ 13 C OM as a proxy of proportion of algal biomass in sediments) and community composition (PC1 pig ). These results confirm previous findings that the zooplankton diet and basal resources are closely linked, and that climate change is responsible for those changes (Belle et al, 2019;Rantala et al, 2015). thic and pelagic consumers in the long term (Belle et al, 2017(Belle et al, , 2018(Belle et al, , 2020.…”
Section: Trends and Fluctuations In Climate Algal Community And Carbon Resources For Zooplanktonsupporting
confidence: 91%
“…shown that zooplankton consumers in subarctic lakes are mainly fuelled by aquatic resources (Belle et al, 2019;Rantala et al, 2015). In the present study, δ 13 C values of cladoceran resting eggs (δ 13 C Clado ) ranged from −35.2‰ to −30.9‰, also indicating the preferential assimilation of 13 C-depleted aquatic basal resources by primary consumers.…”
Section: Trends and Fluctuations In Climate Algal Community And Carbon Resources For Zooplanktonsupporting
confidence: 49%
“…Combined uses of chitinous remains and stable isotopes in paleolimnological studies have been developed to reconstruct long-term dynamics of past carbon flows through food webs (Heiri et al 2012;van Hardenbroek et al 2018;Belle et al 2019), and this time-for-time approach provides a reliable alternative to the widely used space-for-time approach. Specifically, head capsules of Chironomidae larvae (Arthropoda; Diptera; Nematocera), non-biting midges with larvae growing in superficial lake sediments, are morphologically and chemically well preserved in sediments (Verbruggen et al 2011a, b) and can therefore be utilized for carbon stable isotope analysis (expressed as δ 13 C).…”
Section: Aquatic Sciencesmentioning
confidence: 99%
“…A 100-cm sediment core retrieved from the deepest part of the lake, and age-depth model showed that the core covered the last ca. 9500 years, and the model was already discussed in Belle et al (2019). Briefly, the deglaciation of the surroundings of Lake Diktar Erik started at ca.…”
Section: Study Site For Paleolimnological Reconstructionmentioning
confidence: 99%
“…Sedimentary proxies, such as organic matter concentration, carbon and nitrogen stable isotopes, carbon and nitrogen concentrations, and C/N weight ratios, were analysed to reflect both terrestrial and aquatic processes. A principal component analyses (PCA) was performed on sediment data (already published in Belle et al, 2019), and the first PCaxis scores are used as a marker of climate-induced…”
Section: Study Site For Paleolimnological Reconstructionmentioning
confidence: 99%